Stress-Testing Croatian Households with Debt : Implications for Financial Stability - Zalduendo, Juan; Sugawara, Naotaka (2012)
The purpose of this paper is to stress test the resilience of Croatian households with debt to economic shocks. The shocks not only impact a household's welfare, but also increase the probability of loan default. As a result, there is a direct link between these stress-testing exercises and financial stability risks. The authors find that very few households are at risk as a result of the shocks experienced over the past few years; new vulnerable households represent about 2 percent of all households, 6 percent of households with debt, and 2-3 percent of aggregate banking system assets. This suggests that household over-indebtedness in Croatia is unlikely to become a drag on aggregate economic activity and that financial stability risks remain manageable. One caveat should be noted. Some 27-31 percent of households with debt, representing 8-9 of banking system assets, are vulnerable even before being subjected to an economic shock. Since NPLs were low before the global financial crisis, it can be argued that banks knew something about some of these households that is not captured by household budget surveys. It follows that the calculations in this paper should primarily focus on the increased vulnerability of households as a result of shocks and are likely to represent an upper bound to the financial stability risks faced by Croatia on account of household indebtedness.